Diffusion of Ions in Phosphonium Orthoborate Ionic Liquids Studied by 1H and 11B Pulsed Field Gradient NMR - Filippov, Andrei; Munavirov, Bulat; Glavatskih, Sergei; Shah, Faiz Ullah; Antzutkin, Oleg N. (Frontiers in Chemistry, 2020)
Non-halogenated boron-based ionic liquids (ILs) composed of phosphonium cations and chelated orthoborate anions have high hydrolytic stability, low melting point and exceptional properties for various applications. This study is focused on ILs with the same type of cation, trihexyltetradecylphosphonium ([P6,6,6,14]+), and two orthoborate anions, such as bis(salicylato)borate ([BScB]−) and bis(oxalato)borate ([BOB]−). We compare the results of this study with our previous studies on ILs with bis(mandelato)borate ([BMB]−) and a variety of different cations (tetraalkylphosphonium, dialkylpyrrolidinium and dialkylimidazolium). The ion dynamics and phase behavior of these ILs is studied using 1H and 11B pulsed-field-gradient (PFG) NMR. PFG NMR is demonstrated to be a useful tool to elucidate the dynamics of ions in this class of phosphonium orthoborate ILs. In particular, the applicability of 11B PFG NMR for studying anions without 1H, such as [BOB]−, and the limitations of this technique to measure self-diffusion of ions in ILs are demonstrated and discussed in detail for the first time.